Poland - Mazowieckie Public Expenditure Review Local Responses to the Global Economic Crisis - World Bank (World Bank, 2012)
This report examines the fiscal prospects of major units of sub-national government in the voivodship (province) of Mazowieckie and proposes a series of reforms in recurrent spending and capital investment planning. Mazowieckie, the seat of Warsaw, is the heart of the Polish economy. While Poland is weathering the current global economic downturn fairly well, the sub-national governments of Mazowieckie face considerable fiscal uncertainties. A long period of rising revenues has come to an end. At the same time, both the province and the City of Warsaw are embarked upon major programs of capital investment. While European Union (EU) funds could help finance some of these investments, there is evidence that the money from Brussels is not reaching the highest priority projects. The objective of this report is to examine how the major units of sub-national government can respond - how they can restrain the growth of deficits and allocate funds more wisely. The report is organized in four sections. The first describes the regional, macroeconomic, and institutional context of the sub-national governments. The following three sections examine the fiscal situation of Warsaw; the Voivodship, and three case study'cities.